2009
DOI: 10.1093/nar/gkp135
|View full text |Cite
|
Sign up to set email alerts
|

Silencing by nuclear matrix attachment distinguishes cell-type specificity: association with increased proliferation capacity

Abstract: DNA loop organization by nuclear scaffold/matrix attachment is a key regulator of gene expression that may provide a means to modulate phenotype. We have previously shown that attachment of genes to the NaCl-isolated nuclear matrix correlates with their silencing in HeLa cells. In contrast, expressed genes were associated with the lithium 3,5-diiodosalicylate (LIS)-isolated nuclear scaffold. To define their role in determining phenotype matrix attached regions (MARs) on human chromosomes 14–18 were identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…The small number of attachment sites observed in the studied 167 kb region comprising the TP53 gene locus is in agreement with the previous study of Linnemann and Krawetz [2009b]. They have shown, by screening human chromosomes 14-18, a correlation between high gene density and low number of MARs.…”
Section: Discussionsupporting
confidence: 92%
“…The small number of attachment sites observed in the studied 167 kb region comprising the TP53 gene locus is in agreement with the previous study of Linnemann and Krawetz [2009b]. They have shown, by screening human chromosomes 14-18, a correlation between high gene density and low number of MARs.…”
Section: Discussionsupporting
confidence: 92%
“…A subset of sperm RNAs may also serve to structurally support the nuclear matrix (Linnemann 2009). This proteinaceous network present in most cells functionally organizes the genome by binding discreet regions of DNA at sequences termed Scaffold/Matrix Attachment Regions (S/MARs).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of p53 expressing and p53 null tumors has revealed that the loss of this nuclear matrix binding protein allows a cell to escape from the normal G1 arrest of the cell cycle during which DNA damage is repaired[47]. This loss of binding to the nuclear matrix may disrupt the normal local looping patterns and expose origins of replication or result in the loss of nuclear matrix associated gene silencing [30]. In turn, this would likely result in the aberrant expression of proteins that allow progression through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Both HTR-F and HTR-M, matrix and loop DNA were isolated after optimal extraction as described [29] [30]. Briefly, the halo structures were gently washed with REact® 3 restriction buffer (Invitrogen, Carlsbad, CA, USA) for 20 minutes at room temperature then centrifuged at 1000 × g at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation